Penggunaan Ultrasound di Anestesi Obstetri - Apsari, Ratih Kumala Fajar; Uyun, Yusmein (Jurnal Komplikasi Anestesi, 2018)
The incidence of complex medical problems in obstetric populations is is rising, and anesthesia for parturient patients add another problem in this complexity. Ultrasound provides an accurate visualization of the internal anatomical structures that may help assess clinical conditions and improve the safety of therapeutic interventions. Ultrasound procedures in obstetric anesthesia have been used in guiding the neuraxial block, transversus abdominis plane block for post-caesarean section pain control, and vascular access. Ultrasound may also be performed to assess gastric volume, airway evaluation in critical obstetric patients, lung evaluation, transesophageal echocardiography, and intracranial pressure assessment as a surrogate marker of preeclampsia. To succeed in ultrasound guidance techniques, it requires familiarity with relevant cross sectional anatomy. Knowledge of anatomy, without any understanding of its structural formation on ultrasound will hamper the understanding of ‘sonoanatomy’.